Pannexin 1 channels in skeletal muscles - Cea, Luis A.; Riquelme, Manuel A.; Vargas, Anibal A.; Urrutia, Carolina; Sáez, Juan C. (Frontiers in Physiology, 2014)
Normal myotubes and adult innervated skeletal myofibers express the glycoprotein pannexin1 (Panx1). Six of them form a “gap junction hemichannel-like” structure that connects the cytoplasm with the extracellular space; here they will be called Panx1 channels. These are poorly selective channels permeable to ions, small metabolic substrate, and signaling molecules. So far little is known about the role of Panx1 channels in muscles but skeletal muscles of Panx1-/- mice do not show an evident phenotype. Innervated adult fast and slow skeletal myofibers show Panx1 reactivity in close proximity to dihydropyridine receptors in the sarcolemma of T-tubules. These Panx1 channels are activated by electrical stimulation and extracellular ATP. Panx1 channels play a relevant role in potentiation of muscle contraction because they allow release of ATP and uptake of glucose, two molecules required for this response. In support of this notion, the absence of Panx1 abrogates the potentiation of muscle contraction elicited by repetitive electrical stimulation, which is reversed by exogenously applied ATP. Phosphorylation of Panx1 Thr and Ser residues might be involved in Panx1 channel activation since it is enhanced during potentiation of muscle contraction. Under denervation, Panx1 levels are upregulated and this partially explains the reduction in electrochemical gradient, however its absence does not prevent denervation-induced atrophy but prevents the higher oxidative state. Panx1 also forms functional channels at the cell surface of myotubes and their functional state has been associated with intracellular Ca2+ signals and regulation of myotube plasticity evoked by electrical stimulation. We proposed that Panx1 channels participate as ATP channels and help to keep a normal oxidative state in skeletal muscles.